2013
DOI: 10.1016/j.ssresearch.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Labor market penalties for foreign degrees among college educated immigrants

Abstract: Are college degrees earned abroad worth less in the American economy than degrees earned in the United States? Do the labor market penalties associated with holding a foreign degree vary as a function of the country or region in which it was earned? Do these processes differ for men and women? We use data on 18,365 college-educated immigrants from the National Survey of College Graduates (NSCG) to address these questions. Female immigrants with foreign degrees are less likely to be employed than immigrant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
1
37
1
Order By: Relevance
“…Prior research on immigrants' major-job match suggested an association between foreign status and major-job match, meaning that foreign workers tend to hold jobs unrelated to their college majors. Exclusively focusing on foreign immigrants, most of whom were not trained within the U.S. educational system, prior research found that immigrants were more likely to hold jobs unrelated to their college major in their host country compared to domestic workers (Arbeit & Warren, 2013;Dean, 2009;Frank, 2009;Trevelyan & Tilli, 2010). Previous research also revealed the likelihood of mismatch between education and jobs is greater among immigrants with college degrees from their home country than those who received college degrees from their host country (Arbeit & Warren, 2013;Dean, 2009;Frank, 2009;Trevelyan & Tilli, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research on immigrants' major-job match suggested an association between foreign status and major-job match, meaning that foreign workers tend to hold jobs unrelated to their college majors. Exclusively focusing on foreign immigrants, most of whom were not trained within the U.S. educational system, prior research found that immigrants were more likely to hold jobs unrelated to their college major in their host country compared to domestic workers (Arbeit & Warren, 2013;Dean, 2009;Frank, 2009;Trevelyan & Tilli, 2010). Previous research also revealed the likelihood of mismatch between education and jobs is greater among immigrants with college degrees from their home country than those who received college degrees from their host country (Arbeit & Warren, 2013;Dean, 2009;Frank, 2009;Trevelyan & Tilli, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to this literature, there seems to be only a handful of studies focusing on returns to origin‐ as opposed to destination‐country qualifications, particularly regarding foreign degrees . Arbeit and Warren () compare immigrants holding a foreign degree with immigrants who obtained their college degree in the USA using the National Survey of College Graduates (NSCG), and find higher wage returns in favour of immigrants with US degrees. Even after allowing for selection into employment, both male and female foreign degree holders are still found to be associated with lower earnings, except for degrees earned in Canada, the UK and Ireland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The negative impact of foreign education is well documented in more general studies of immigrant integration where it is thought to reflect a number of factors including: the imperfect knowledge by employers of foreign degrees; the lower quality of foreign education; the internal labour markets created by professional associations that demand recertification for the trades and the professionally trained; and the use of foreign education by employers to discriminate statistically in favour of those who are educated in the destination country (Arbeit and Warren, ; Boyd and Thomas, ; Buzdugan and Halli, ; Kanas and van Tubergen, ). Additionally, compared with those educated in the destination country, foreign education may indirectly be capturing the effects of less acculturation and/or later ages of arrival for the immigrant population (Tong, ).…”
Section: Matching Stem Fields Of Study To Work and Wages: The Roles Omentioning
confidence: 99%